2011
DOI: 10.1093/infdis/jir068
|View full text |Cite
|
Sign up to set email alerts
|

Closer to the Goal: Efforts in Measles Elimination in Germany 2010

Abstract: Increasing 2-dose vaccination coverage has led to an interruption of endemic measles virus circulation in Germany. However, outbreaks after virus importation still occur and contribute to international transmission chains. Between 2003 and 2009, annual measles incidence ranged between 0.2 and 2.8 per 100,000 population. Immunization gaps have been identified especially in secondary-school students and young adults, which is also reflected by a shift in age distribution of reported measles cases toward older ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…These differences can be largely explained by local differences in vaccination coverage and population immunity 8 , 9 . Several possible reasons for these differences in vaccine uptake have already been discussed 22 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences can be largely explained by local differences in vaccination coverage and population immunity 8 , 9 . Several possible reasons for these differences in vaccine uptake have already been discussed 22 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found that measles incidence in the western area followed a constantly decreasing trend between 2007 and 2011. This encouraging trend may be associated with concerted programmes of health education and a catch-up campaign of measles vaccination, as well as the efforts to increase vaccination coverage at school entry that followed the large-scale outbreak of measles that occurred in North Rhine-Westphalia in 2006 8 . The proportion of children in North Rhine-Westphalia who had received a second dose of measles vaccine at school entry increased from 74.7% in 2005 to 94.1% in 2011 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the reduction in the number of children affected by measles, changes in the epidemiology of the disease are to be expected, as has been experienced in other countries14,15). To maintain the elimination status of measles in Korea, ongoing efforts are needed to meet the goals of: 1) high vaccination coverage for 2 doses of MMR vaccine, and 2) building effective measles surveillance strategies16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Recent outbreaks showed an immunization gap in adolescents and young adults ( 6 ). Consequently, outbreaks still occur in Germany every year, although recently they have been more limited in number of cases, length of time, and extent of national transmission ( 7 , 8 ). A total of 915 measles cases were reported in 2008, 571 in 2009, and 780 in 2010; incidence was 7–10 cases/1 million population (www3.rki.de/SurvStat/QueryFormaspx).…”
mentioning
confidence: 99%